PASAR EKSTRIM SEBAGAI DESTINASI WISATA DI KOTA TOMOHON - Fredy J. Binambuni (HOLISTIK, Journal of Social and Culture, 2023)
Tourism is still one of the mainstay sectors for developing countries, including in this case Indonesia. For developing countries, this sector includes priorities to increase the country's foreign exchange, besides that tourism is a new style industry that is able to spur rapid economic growth in terms of employment opportunities, income, standard of living, and in activating other sectors in tourist receiving countries. What do we think of when we hear about the market? Of course we agree that the market is a place to make buying and selling transactions. Whether it's a market that sells a variety of raw foods or traditional markets, or modern markets like most of us encounter around us. However, there is one market that is considered the most extreme and invites a lot of curiosity from various parties. Its name is Tomohon Market, a meat market with the most extreme nickname. Tomohon Market is one of the attractions of tourists from outside the region, even other countries who come to visit this extreme market, because this market presents or sells various types of animals or animals such as; Wild boars, forest rats, bats, snakes, monkeys and so on that make this market known or said to be an extreme market Animals sold, how to execute animals or killed at the point of sale so that people immediately see them, as is the case with dogs and cats, these two animals are often the center of attention from outside people who come to visit the market. Keywords : eco tourism, extreme market, tourism